2012
DOI: 10.1302/0301-620x.94b10.28673
|View full text |Cite
|
Sign up to set email alerts
|

Does the posterolateral bundle influence rotational movement more than the anteromedial bundle in anterior cruciate ligament reconstruction?

Abstract: The biomechanical function of the anteromedial (AM) and posterolateral (PL) bundles of the anterior cruciate ligament (ACL) remains controversial. Some studies report that the AM bundle stabilises the knee joint in anteroposterior (AP) translation and rotational movement (both internal and external) to the same extent as the PL bundle. Others conclude that the PL bundle is more important than the AM in controlling rotational movement. The objective of this randomised cohort study involving 60 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In addition, no patients presented "abnormal" or "severely abnormal" knee laxity or graft failures at the 2-year follow-up. These data corroborate previous studies that showed low graft failure incidence in patients submitted to double-bundle reconstruction [13,25]. Moreover, the present outcomes referring to normal function, satisfactory stability, and an absence of post-operative complications allow the authors of this study to affirm that double-bundle reconstruction without tibial implants is a safe technique and provides similar outcomes than other technique with four implants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, no patients presented "abnormal" or "severely abnormal" knee laxity or graft failures at the 2-year follow-up. These data corroborate previous studies that showed low graft failure incidence in patients submitted to double-bundle reconstruction [13,25]. Moreover, the present outcomes referring to normal function, satisfactory stability, and an absence of post-operative complications allow the authors of this study to affirm that double-bundle reconstruction without tibial implants is a safe technique and provides similar outcomes than other technique with four implants.…”
Section: Discussionsupporting
confidence: 91%
“…Several biomechanical [28][29][30] and clinical studies [11,13,19] have investigated the relevance of additional posterolateral (PL) bundle on knee transversal plane stability. Recent systematic review reported superior clinical results in relation to the anterior and rotational stability in patients who received an anatomic double-bundle technique when compared to a single-bundle technique [27].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The double-bundle method aims to reconstruct both the anteromedial (AM) and posterolateral (PL) bundles of the native ACL at their sites of insertion. However, recent studies have shown that central anatomical singlebundle ACL reconstruction can also restore normal knee function.…”
mentioning
confidence: 99%
“…Moreover, Komzák et al. reported that reconstruction of the AM bundle had a greater effect on reducing internal rotation than reconstruction the PL bundle 30 . The addition of anterolateral ligament reconstruction may be desirable in patients who have massive rotational knee instability.…”
Section: Discussionmentioning
confidence: 99%